A review of the genus Sphingius Thorell, 1890 from India (Araneae: Liocranidae) - Sankaran, Pradeep M.; Caleb, John T.d.; Sebastian, Pothalil A. (Zootaxa, 2020)
Indian species in the genus Sphingius Thorell, 1890 are revised, mostly based on the type material available in the National Zoological Collection, Zoological Survey of India, Kolkata. Sphingius barkudensis Gravely, 1931, S. nilgiriensis Gravely, 1931 and S. paltaensis Biswas & Biswas, 1992 are redescribed. Two new combinations and one new synonymy are recognised: S. longipes Gravely, 1931 is transferred to the cithaeronid genus Inthaeron Platnick, 1991 and S. kambakamensis Gravely, 1931 is transferred to the corinnid genus Cambalida Simon, 1909, while S. delakharae Pawaria, Bodkhe, Kamble, Uniyal & Talwar, 2018 syn. nov. is synonymised with S. barkudensis. Images of all the examined type material are provided.